2021
DOI: 10.1186/s13195-021-00802-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma pTau181 predicts cortical brain atrophy in aging and Alzheimer’s disease

Abstract: Background To investigate the association of plasma pTau181, assessed with a new immunoassay, with neurodegeneration of white matter and gray matter cross-sectionally and longitudinally, in aging and Alzheimer’s disease. Methods Observational data was obtained from the Alzheimer’s Disease Neuroimaging Initiative, in which participants underwent plasma assessment and magnetic resonance imaging. Based on their clinical diagnosis, participants were cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 36 publications
6
42
0
Order By: Relevance
“…This corroborates the framework in which pTau181 appears at later stages of the disease, when hippocampal atrophy is more prominent. 22 For the established AD biomarker CSF pTau181, rates of concordance and discordance differed widely between analyses. It is important to note that not all participants of the TRIAD cohort underwent a lumbar puncture, lowering the number of individuals in the above results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This corroborates the framework in which pTau181 appears at later stages of the disease, when hippocampal atrophy is more prominent. 22 For the established AD biomarker CSF pTau181, rates of concordance and discordance differed widely between analyses. It is important to note that not all participants of the TRIAD cohort underwent a lumbar puncture, lowering the number of individuals in the above results.…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates the framework in which pTau181 appears at later stages of the disease, when hippocampal atrophy is more prominent. 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was subsequently verified by others ( Lewczuk et al, 2004 ; Fagan et al, 2011 ; Tang et al, 2014 ) and later also was confirmed with the measurement of serum ptau181 ( Shekhar et al, 2016 ). Recent studies demonstrated that blood ptau181 can predict cortical brain atrophy ( Llibre-Guerra et al, 2019 ; Tissot et al, 2021 ), tau and amyloid-beta pathology ( Lantero Rodriguez et al, 2020 ; Clark et al, 2021 ; Moscoso et al, 2021b ), differentiate AD from other neurodegenerative diseases ( Mielke et al, 2018 ; Thijssen et al, 2020 ; Grothe et al, 2021 ) and identify AD across the clinical continuum ( Janelidze et al, 2020a ; Karikari et al, 2020b , 2021 ). In familial AD, plasma ptau181 levels may rise as early as 16 years before clinical onset ( O’connor et al, 2020 ).…”
Section: Properties Of Neurofilaments Relevant To Their Use As Biomarkersmentioning
confidence: 99%
“…Ji et al (14) used MRI to extract the voxel features of the brainstem for research and confirmed that early AD is caused by brainstem atrophy. Tissot et al (15) used voxelbased morphometry to detect the association between plasma phosphorylation-tau181 (p-tau181) and neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%